Analisis Hukum Terhadap Investasi Bodong Berkedok Syariah: Studi Kasus DSI di Indonesia dan Perlindungan Investor di Indonesia - Kgs. M. Iqbal saputra; M. Krisna; Nada Nurizki; Holijah . (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rise of fraudulent investments disguised as sharia in Indonesia, including the case of the Indonesian Sharia Fund (DSI), reflects low public financial literacy and the misuse of sharia terminology. This study aims to analyze the fraudulent methods used by DSI and the effectiveness of legal protection for investors in Indonesia. The method used is qualitative research with a normative juridical approach, utilizing secondary data in the form of laws and regulations, literature, and scientific journals, without the use of quantitative data or statistical analysis. The results indicate that DSI practices contain elements of gharar and fraud, and that supervision and education remain weak. Investor protection is suboptimal due to constraints in regulatory implementation. Therefore, it is necessary to strengthen supervision by the Financial Services Authority and improve public financial literacy.